Avaliação do método de coacervação para produção de sistemas micro/nanoestruturados a base de derivados celulósicos - Estevam, Taynara Oliveira (2022)
The microencapsulation process based on the complex coacervation method continues to be widely studied, it’s can be used in the production of micro and nanocapsules of interest for a wide range of applications likes pharmaceutical, food until agricultural industries. However, several aspects of the coacervation phenomenon affect the procedure of encapsulation and núcleos formation. A better understanding of how polymer structure affects the complex coacervates formation must be constantly improved and refined to produce capsules with adequate properties. In this sense, the aims of present work is to evaluate the obtainment of micro/nanocapsules from cellulosic derivatives such as Carboxymethylcellulose (CMC) from different molar mass (two distinct suppliers) and Hydroxypropylmethylcellulose (HPMC) as matrices, Tylose (Hydroxyethylcellulose-HEC) as an emulsifier and macauba oil as material core by the complex coacervation method. The matrices were characterized by the presence of functional groups (FTIR), thermal behavior (TGA) and viscosimetric molar mass determination. It were prepared many formulations in the different concentrations with theses materials. The viscosimetric molar masses obtained were 2.3156 x 105 g.mol-1 and 4.1157 x 105 g.mol-1 for CMC AMTEX and EMFAL, and 3.2078 x 105 g.mol-1 for HPMC, respectively. The best results were observed for formulation I, prepared with 72% HPMC, 10% CMC AMTEX and 18% macaúba oil, in which the microcapsules had dimensions around 197.1 nm, observed by electron microscopy and with 72.0% of oil encapsulation capacity. The results showed that the CMC-AMTEX/HPMC par had a good interaction due to the lower molar mass of CMC-AMTEX then CMC-EMFAL. On the other hand, the emulsifier choosed (Tylose) didn’t influence on the formation and encapsulation of macaúba oil in the nanocapsules.